Feasibility and acceptability of wrist actigraph in assessing sleep quality and sleep quantity: a home-based pilot study in healthy volunteers* - Mohamad Noor, Zaswiza; Smith, Alesha J.; Smith, Simon S.; Nissen, Lisa M. (Scientific Research Publishing Inc., 2013)
Purpose: This study aimed to determine the feasibility and acceptability of actigraphy to monitor sleep quality and quantity in healthy self-rated good sleeper adults at home-based settings. Method: Sixteen healthy volunteers (age >18) were invited to participate. Each participant was provided with a wrist actigraph device to be worn for 24-hours/day for seven consecutive days to monitor their sleep-wake patterns. Actigraphy data was downloaded using proprietary software to generate an individual sleep report. Participants also completed a set of self-reported Health Related Quality of Life (HRQOL) using WHO (five) Well Being Index (WBI) questionnaires. Results: Actigraphy was well accepted by all participants. Only 43.8% of the participants achieved normal total sleep time (TST) and 62.5% had a mean sleep efficiency value below the normal range. Despite a reduced quality of sleep among the participants, the self-reported HRQOL scores produced by the WHO-5 WBI showed a ‘fair’ to ‘good’ among the participants. Conclusions: To maintain healthy wellbeing, it is vital to have efficient and quality sleep. Insufficient and poor sleep may contribute to various health problems and hazardous outcomes. People often believe they have normal and efficient sleep, not realising they may be developing poor sleep habits. This study found that actigraphy can be easily utilized to monitor sleep-wake patterns at home-based settings. We proposed that actigraphy could be adapted for use in the primary care settings (e.g. community pharmacy) to improve the sleep health management in the community.